KONTRIBUSI METODOLOGIS FAZLUR RAHMAN DALAM STUDI HADIS (SUNNAH) - Zuhri Humaidi (IAIN Kediri, 2018)
In Islamic study especially in Islamic law study, study on hadith has been conducted. However, it is often that the resulted works tend to one of two tendencies namely absolutism and skeptics. The absolutism paradigm is developed in traditional Islamic study; meanwhile, skeptics paradigm is grown among orientalist and Muslim scholars oriented to West. This article discusses the ideas of Fazlur Rahman, one of contemporary Muslim scholars having popular works in Indonesia since the last year of 90. Rahman tried to formulate the basis of history study and hadith methodology that use both traditional Islamic knowledge and some important findings of orientalists. It is really useful thought, enriches hadith study, and also Islamic study in general. Keywords; Sunnah, lively sunnah, absolutism, sceptism